Are There Abnormalities in Peripheral and Central Components of Somatosensory Evoked Potentials in Non-Specific Chronic Low Back Pain? - Puta, Christian; Franz, Marcel; Blume, Kathrin R.; Gabriel, Holger H. W.; Miltner, Wolfgang H. R.; Weiss, Thomas (Frontiers in Human Neuroscience, 2016)
Chronic low back pain (CLBP) was shown to be associated with longer reflex response latencies of trunk muscles during external upper limb perturbations. One theoretical, but rarely investigated possibility for longer reflex latencies might be related to modulated somatosensory information processing. Therefore, the present study investigated somatosensory evoked potentials (SEPs) to median nerve stimulation in CLBP patients and healthy controls (HC). Latencies of the peripheral N9 SEP component were used as primary outcome. In addition, latencies and amplitudes of the central N20 SEP component, sensory thresholds, motor thresholds, and nerve conduction velocity were also analyzed in CLBP patients and HC. There is a trend for the CLBP patients to exhibited longer N9 latencies at the ipsilateral Erb’s point compared to HC. This trend is substantiated by significantly longer N9 latencies in CLBP patients compared to normative data. None of the other parameters showed any significant difference between CLBP patients and HC. Overall, our data indicate small differences of the peripheral N9 SEP component; however, these differences cannot explain the reflex delay observed in CLBP patients. While it was important to rule out the contribution of early somatosensory processing and to elucidate its contribution to the delayed reflex responses in CLBP patients, further research is needed to find the primary source(s) of time-delayed reflexes in CLBP.